Transport Measurements across 47°N in the North Atlantic, Cruise No. MSM64, May 27 - June 02 - June 23, 2017, Southampton (UK) - Galway (Ireland) - St. John's (Canada) - Kieke, Dagmar; Altona, Karim; Buinyi, Aleksei; Dos Santos Ferreira, Christian; Frahm, Laura; Garcia Quintana, Yarisbel; Gerken, Jan; Gerriets, Andrea; Herland, Asmund; Kinne, Stefan; Köllner, Manuela; Küper, Svea; et al. (Gutachterpanel Forschungsschiffe, 2019)
Cruise MSM64 with RV MARIA S. MERIAN consisted of two legs. The shorter leg 1 (Southampton-Galway, May 27th to June 02nd, 2017) focussed on the calibration of the newly installed multi-beam echo-sounder Kongsberg EM712 for shallow water applications and its respective sea acceptance test as well as a recalibration of the Kongsberg EM122 multi-beam echo-sounder for deep water applications. The longer leg 2 (Galway-St. John's, June 02nd to June 23rd, 2017) dealt with investigating the water column characteristics and strength of the oceanic circulation system along two survey lines located in the southern subpolar North Atlantic: the so-called 47°/48°N section and a survey line running parallel to the western flank of the Mid-Atlantic Ridge (MAR). : MARIA S. MERIAN-Berichte